Prophylactic cranial irradiation in extensive disease small cell lung cancer: An endless debate. (November 2019) - Picardi, Cristina; Caparroti, Francesca; Di Maio, Massimo; Kaššák, Filip; Banna, Giuseppe Luigi; Addeo, Alfredo
Graphical abstract: Patient-specific management depending on initial employment of PCI. Abbreviations: PCI: prophylactic cranial irradiation; BM: brain metastases, WBRT: whole-brain radiotherapy; HA: hippocampal avoidance; SRS: steretoctic radiosurgery; Fx: fractions. Highlights: PCI significantly decreases incidence of BM in ED-SCLC in patients with at least partial response to first-line systemic treatment. More than 60% of patients not receiving PCI develop BM. Impact on OS is disputed since the publication of a JCOG trial suggesting that close MRI-surveilled patients do not have worse OS than those treated with PCI. International guidelines currently suggest to consider PCI or MRI brain surveillance in ED-SCLC with complete or partial response to first line chemotherapy. PCI toxicity is rather mild and QoL of patients after PCI might be better than after salvage brain radiotherapy. Hippocampal avoidance could decrease NCF decline. No known prognostic factors allow to individualize therapeutic management. Individual patient-oriented approach is crucial and clinical discussion should include all pros and cons of PCI so that patients can make an informed decision. Abstract: Extensive disease Small cell lung cancer (ED-SCLC) represents a very aggressive malignancy in which brain metastases (BM) are quite common. Clinical trials on prophylactic cranial irradiation (PCI) have showed a clear decrease in the risk of developing BM but conflicting results concerning a possible survival advantage. A landmark European Organisation for Research and Treatment of Cancer (EORTC) prospective trial, as well as multitude of retrospective series confirm survival benefit after PCI. Recently, a Japan Clinical Oncology Group (JCOG) study did not find such survival benefit, provided that non-irradiated patients are closely followed by MRI. Henceforth, the role of PCI in this population has been questioned, on the ground of the possible absence of survival benefit, leading to a gradual shift in oncology practice. We performed a review of the literature on the subject of PCI in ED-SCLC patients. We conclude that PCI could still play a crucial role in these patients, considering not only a possible survival benefit, but also alternative endpoints, such as improved local control, delay in the onset of symptomatic BM and lower toxicity of a prophylactic- rather than an eventual active-intent treatment. Individualized attitude should be discussed with patients, while addressing all arguments in favour and against PCI.